Efek Madu Lebah Hutan (Apis dorsata Fabr.) Berbagai Konsentrasi Terhadap pH dan Uji Organoleptik Susu Ultra High Temperature (UHT) - Selawati Palilati; Fahrullah; Ishak Korompot (Food Scientia : Journal of Food Science and Technology, 2021)
The research aims to observe the effect of addition wild honey (Apis dorsata Fabr.) on pH and organoleptic values of ultra high temperature milk (UHT). The research was done using an experimental method using a non-factorial completely randomized design with five levels using SPSS 16. Different concentrations of wild honey (A1= control; A2= 5%; A3= 10%; A4= 15% and A5=20%) were used. The data was statistically analyzed using analysis of variance (ANOVA) with 5% significance level and further processed with Duncan's Multiple Range Test (DMRT). Organoleptic tests for colour, taste and overall preference were also done using qualitative tests (scores). The value of pH gave a significant value (P<0,01) between treatment. The higher the use of wild honey concentration, the lower the pH value produced. The higher the concentration of wild honey, the higher the organoleptic value. The best treatment in terms of colour, taste, and level of preference was observed in the sample with the 20% honey concentration, each of which resulted in an average score of 4.